Indonesia vs Japan in the Education System - Riza Desriandi; Joni Indra Wandi; Rhona Sandra; Erda Fitriani; Nurhizrah Gistituati; Rusdinal Rusdinal; Azwar Ananda (Postgraduate School, Universitas Negeri Padang, 2022)
This study aims to compare Indonesian and Japanese education by using five indicators, namely the purpose of education, education management, education budget, education personnel, and salaries, as well as the learning evaluation process. The education system according to the National Education System Law No. 20/2003 it is stated that the National Education System is all components of education that are interrelated in an integrated manner to achieve national education goals. This research is based on a literature study by looking for theoretical references that are relevant to the cases or problems found. The results of this study According to Law No. 20 concerning